‘Sometimes they fail to keep their faith in us’: Community health worker perceptions of structural barriers to quality of care and community utilisation of services in Bangladesh - Puett, Chloe; Alderman, Harold; Sadler, Kate; Coates, Jennifer (Wiley, 2015)
Community health workers (CHWs) have strong potential to extend health and nutrition services to underserved populations. However, CHWs face complex challenges when working within weak health systems and among communities with limited abilities to access and utilise CHW services. It is crucial to understand these challenges to improve programme support mechanisms. This study describes the results of qualitative investigations into CHW perceptions of barriers to quality of care among two groups of workers implementing community case management of acute respiratory infection, diarrhoea and severe acute malnutrition in southern Bangladesh. We explored systemic barriers to service delivery, pertaining to communities and health systems, which limited the usefulness and effectiveness of CHW services. Focus group discussions (n = 10) were conducted in March 2010. Discussions were analysed for themes related to CHWs' work challenges. Findings highlight several perceived barriers to effective service provision, including community poverty constraining uptake of recommended practices, irregular supplies of medicine from the health facility and poor quality of care for CHW referrals sent there. This study further documents interactions between demand‐side and supply‐side constraints including the influence of health system resource constraints on community trust in CHW services, and the influence of community resource constraints on the utilisation and effectiveness of CHW services. By documenting service delivery challenges from the perspective of the frontline workers themselves, this article contributes evidence to help identify appropriate support mechanisms for these workers, in order to develop scalable and sustainable CHW programmes in countries with under‐resourced public health care infrastructure.